2020
DOI: 10.1016/j.ejvs.2020.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of the Extracellular Matrix Related Genes COL15A1, CHRDL2, EFEMP1, and TIMP1 in Varicose Veins

Abstract: Methods. Thirty-three patients with severe PTS were included in the study. Group 1 with 11 patients, underwent IFS stenting. Group 2 with 22 patients, had hybrid procedures: open endovenectomy from the common femoral vein (CFV) with arteriovenous fistula creation and iliac vein stenting. Pre-operatively all patients were evaluated with ultrasound and contrast venography. There was no difference between the groups for demographic data, comorbidities, and the results of imaging studies. The distribution of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One of the biggest genome-wide association studies (GWASs) on VVs was performed by the American 23andMe company scientists who identified a group of 12 SNPs and genes corresponding to them: rs507666 (ABO), rs966562 (XKR5, ANGPT2, AGPAT5), rs7111987 (ADM, AMPD3), rs11121615 (CASZ1), rs111434909 (ANGPT1), rs145218303 (ARGHAP6), rs6905288 (VEGFA), rs4516218 (PIEZO1), rs4463578 ( ZIC3, FGF13), rs6062618 (SOX18, TCEA2), rs6712038 (PPP3R1, CNRIP1) and rs79607156 (THEG5, ZNF507) [21] . However, those associations were not replicated.…”
Section: Genetic Association Studies On Varicose Vein Pathogenesis-an Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest genome-wide association studies (GWASs) on VVs was performed by the American 23andMe company scientists who identified a group of 12 SNPs and genes corresponding to them: rs507666 (ABO), rs966562 (XKR5, ANGPT2, AGPAT5), rs7111987 (ADM, AMPD3), rs11121615 (CASZ1), rs111434909 (ANGPT1), rs145218303 (ARGHAP6), rs6905288 (VEGFA), rs4516218 (PIEZO1), rs4463578 ( ZIC3, FGF13), rs6062618 (SOX18, TCEA2), rs6712038 (PPP3R1, CNRIP1) and rs79607156 (THEG5, ZNF507) [21] . However, those associations were not replicated.…”
Section: Genetic Association Studies On Varicose Vein Pathogenesis-an Overviewmentioning
confidence: 99%
“…Quite a few works have been done to replicate top associations from GWASs for VVD using independent datasets. One of them, performed in our laboratory, aimed to verify the associations revealed by Bell et al [21] and Ellinghaus et al [22] using two independent groups of patients: (1) ethnic Russian individuals; and (2) genetic data on a large population-based cohort of British residents obtained from UK Biobank. We also aimed to perform a meta-analysis [25] .…”
Section: Genetic Association Studies On Varicose Vein Pathogenesis-an Overviewmentioning
confidence: 99%